Do Sales Growth, Company Risk, Return on Assets, and Liquidity effect on Tax Avoidance? - Rahma Sari, Indah; Madjid, Suhirman (Taxation and Public Finance, 2023)
This study aims to analyze the effect of sales growth, corporate risk, return on assets and current ratio to tax avoidance. The population in this study is a manufacturing company of pharmaceutical subsectors and health registered in BEI in 2018-2021. The research method used in this research is quantitative method. The sample used in this study were 10 companies, selected based on purposive sampling method. This study uses secondary data obtained through corporate financial statements. The data analysis technique used is multiple linear regression analysis consisting of descriptive statistical analysis, classical assumption test, and hypothesis test. The results of multiple linear analysis showed sales growth variables and ROA had negative effects of tax avoidance. While the risk variable of the company and the current rates have no effect on tax avoidance.